2016
DOI: 10.1136/neurintsurg-2016-012520
|View full text |Cite
|
Sign up to set email alerts
|

Combined endovascular coiling and intra-aneurysmal allogeneic mesenchymal stromal cell therapy for intracranial aneurysms in a rabbit model: a proof-of-concept study

Abstract: This proof-of-concept study shows that adjuvant MSC therapy for intracranial aneurysms is feasible and may enhance histological improvement of coiled aneurysms at 4 weeks post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…Recently published studies demonstrate the benefits of MSCs in promoting intracranial aneurysm healing(53, 58, 71). Rouchaud et al used autologous MSCs from bone marrow directly injected into the aneurysm by endovascular route through a catheter with no scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published studies demonstrate the benefits of MSCs in promoting intracranial aneurysm healing(53, 58, 71). Rouchaud et al used autologous MSCs from bone marrow directly injected into the aneurysm by endovascular route through a catheter with no scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the cells lining the implanted coils would differentiate into arterial endothelial cells and those residing deep to the endothelial lining would become medial smooth muscle cells(13, 53, 54). From a biological perspective, mesenchymal stem cells (MSCs) represent an ideal cell type to populate saccular aneurysms(26, 41, 53, 5558).…”
Section: Introductionmentioning
confidence: 99%
“…The local delivery of mesenchymal stem cells has demonstrated improved aneurysm healing in a rabbit model 18. Controlled release of osteopontin and IL-10,19 vascular endothelial growth factor,20 stromal cell-derived factor 1α (and local delivery of mesenchymal stem cells and endothelial progenitor cells),21 and cyclic peptide SEK-100522 from modified coils have been shown by other groups to accelerate intra-aneurysmal tissue healing in rat models of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…10010-023), while experimental rabbits received an IV injection of 5 × 10 6 MSCs suspended in 2 mL of PBS, both followed with a 2 mL PBS flush. The dose of MSCs selected was in keeping with doses reported in previous studies [20, 21]. Identical injections were also administered on day 15.…”
Section: Methodsmentioning
confidence: 99%
“…The immunomodulatory properties of MSCs can vary based on their environment and have thus been investigated as an adjuvant therapy during the endovascular treatment of cerebral saccular aneurysms [19]. Studies by our laboratory and others have suggested that MSCs introduced at the time of treatment of saccular aneurysms in animal models have the capacity to improve aneurysm histological healing [2022]. However, no studies have been performed to investigate the effects of MSCs on the pathogenesis of saccular aneurysms.…”
Section: Introductionmentioning
confidence: 99%